How women's empowerment influences fertility-related outcomes and contraceptive practices: A cross-sectional study in Mozambique. - Sofia Castro Lopes; Deborah Constant; Sílvia Fraga; Jane Harries (Public Library of Science (PLoS), 2022)
Women's empowerment could be a crucial step for tackling gender inequality and improve women's reproductive health and rights in Mozambique. This study aims to examine how different domains of women's empowerment influence fertility-related outcomes and contraceptive practices in Mozambique. We used the 2015 Demographic Health Survey (DHS) conducted in Mozambique from which a sample of 2072 women aged 15 to 49 years were selected and included in this analysis. A principal component analysis was performed, and the components retained were identified as the domains of empowerment. These were: Beliefs about violence against women, Decision-making, and Control over sexuality and safe sex. A multinomial logistic regression was run to estimate the association between levels of empowerment for each domain and the study outcomes. Crude and adjusted odds ratio (OR) were calculated, with 95% confidence intervals (95% CI). Beliefs about violence against women and Control over sexuality and safe sex were positively associated with having 1 to 4 children. Control over sexuality and safe sex also increased likelihood of women wanting to space childbearing over more than 2 years. Decision-making increased the odds of women not wanting more children. Middle to high empowerment levels for Control over sexuality and safe sex also increased the chances of using any type of contraceptive method and using it for longer periods. All domains, from the middle to high levels of empowerment, decreased the chances of women not wanting to use contraception. Our study confirmed the multidimensional nature of empowerment showing that each domain had a different effect over specific fertility and contraceptive outcomes and reinforced the importance of a domain approach for estimating and understanding empowerment. It also revealed the critical role of Control over sexuality and safe sex domain for improving women's ability to decide over fertility and contraceptive practices in Mozambique.